Second Five Year Plan Programme for 1960-61 Government of Mysore - Planning Commission (Planning Commission, 1960)
This is the last year of the Second Five Year Plan. In the following paragraphs a brief account is given of the progress achieved, and the programme for 1960-61. The Second Plan was implemented from 1st April 1956. the new State of Mysore was formed seven months later, i.e., on 1st November 1956. It became, therefore, necessary to draw a Second Plan for the new State after integration. This Plan includes the plans of the former States of Mysore and Coorg, and the proportionate Plan allocations for the areas transferred from Bombay, Hyderabad and Madras. The programme for 1960-61 and the provisions made therefor.
Government of Mysore